Hacer música en el parque - Vildoso Chirinos, Carmen (2025)
Art workers perform in different spaces, one of which is public space. This article analyzes the case of a cultural activity that has been carried out for fifteen years in a park in the Miraflores district of Lima. It involves a gathering of artists and people of different generations around music, in a dynamic that favors spontaneous participation while cultivating an atmosphere of trust. La Esquina Musical, as it is called, seeks to break down barriers and overcome discriminatory practices through a certain repertoire and a style of cultural animation that promotes socialization. The musicians are key protagonists, which is why the reflection focuses on the profiles of those who have participated in successive ensembles, their trajectories and what these express in relation to the links between art and society in our times, as well as some characteristics of their work. The tensions linked to the use of public space are also examined in a context where some authorities understand their regulatory task in a way that affects the right to enjoyment and emotional well-being.